English Teachers’ Perception on the Merdeka Curriculum, Especially Differentiated Learning at SMAN 2 Bantaeng - Naipon, Adam; Samtidar, Samtidar; Korompot, Chairil Anwar (Journal of Excellence in English Language Education, 2024)
This research aims to determine English teachers perception on the Merdeka Curriculum, especially differentiated learning at SMAN 2 Bantaeng. The method used in this research is descriptive qualitative. Participants in this research were English teachers at SMAN 2 Bantaeng. Two English teachers were selected as research subjects using purposive sampling techniques. The instrument used in this research was a semi-structured interview. The results of this research show that the English teachers at SMAN 2 Bantaeng has a comprehensive understanding of the Merdeka Curriculum, especially differentiated learning. They have implemented it for two years with positive results in improving the quality of learning. Teachers are able to assess and evaluate various aspects of differentiated learning which include content, processes and products. Even though differentiated learning is effective in improving the quality of learning, English teachers still experience various obstacles in its implementation, such as difficulties in obtaining accurate diagnostic test results, recognizing individual student characteristics, choosing appropriate teaching methods or strategies, grouping students effectively, accommodating the diverse learning needs of students, and encourage student independence in completing learning outcomes. Overall, this research found that the English teachers at SMAN 2 Bantaeng had a comprehensive understanding of the Merdeka Curriculum, especially differentiated learning. They have implemented it for two years with positive results in improving the quality of learning. Teachers are able to assess and evaluate aspects of differentiated learning. Even though differentiated learning is effective in improving the quality of learning, English teachers still experience various obstacles in its implementation. This is what makes differentiated learning implementation not standardized.